Impact of marketing mix on customer buying intention: with special reference to selected insurance companies in sri lanka - Arachchige, R.; Weerasiri, S.; Maldeniya, D. (University of Jaffna, 2016)
The objective of this study was to identify the influence of Marketing Mix for customer buying intention of motor insurance in Sri Lanka. History of insurance industry goes to over centuries and currently the industry is facing issues for a profitable growth. Especially the non-life insurance sector ran in a loss for last couple of years and few companies recorded a profit from investment income. But it was not a major issue for non-life insurance section since it operates with the life insurance section. According to the new rules and regulations implemented recently, life insurance and non-life insurance should be segregate into two business entities. Then non-life insurance companies in Sri Lanka will face issues for profitable growth. The researcher tried to find out an acceptable solution for this issue and to introduce recommendations to the insurance industry. The researcher met few senior professionals from insurance companies and got the basic idea about current situation. Also met few ex-professionals from insurance companies and collected information about the insurance industry. It was helped to identify that how the insurance industry was operated before few decades. Then, the researcher developed a sample questionnaire and circulated among 25 respondents. Then the reliability testing was done and developed the final questionnaire. There were 200 respondent had selected to collect primary data. These respondents were selected from the Gampaha district. The data was collected from five insurance companies' customer base. Then identified customers who live in Gampaha district and the questionnaire were circulated through google forms. Both descriptive and inferential techniques were used to analysis the data. Findings review that people is the most influential variable of marketing mix which influence to customer buying intention of motor insurance in Sri Lanka. The place is the next important variable in marketing mix and third important factor is the process of the insurance company. The researchers recommend that to develop the efficiency of people in insurance industry both sales and non sale, improve the customer touch points and to develop the effective and speedy processes to face for industry challenges successfully
Keywords: Buying intention; Customer satisfaction; Customer relationship; Customer expectation; Insurance industry